FIND THE ANSWERS

' a⁴/(a - b)(a - c) + b⁴/(b - c)(b - a) + c⁴/(c - a)(c - b) =    .?

Answer this question

Do you know the correct answer? Make money answering questions! Join now.
  • ' a⁴/(a - b)(a - c) + b⁴/(b - c)(b - a) + c⁴/(c - a)(c - b) =    .?


Answers

a⁴(b-c)+b⁴(c-a)+c⁴(a-b)は、因数分解出来ますか? a⁴(b-c)+b⁴(c-a)+c⁴(a-b)=a⁴(b-c) ...
Read more
Positive: 31 %
Here is an alternative solution to Kb's: WLOG, assume a ≤ b ≤ c. Apply the rearrangement inequality to the 4 sets {a, b, c}, {a, b, c}, {b, c, a}, {c ...
Read more
Positive: 28 %

More resources

set notation. pronunciation. meaning. Venn diagram. answer. A U B "A union B" everything that is in either of the sets {1, 2, 3} A ^ B
Read more
Positive: 31 %
A⁴+b⁴=a²b² ,prove that a⁶+b⁶=0 1. Ask for details; Follow; Report; by Riyo13 06/22/2014. Log in to add a comment Answers ...
Read more
Positive: 26 %
$$A⊆C,B⊆D \quad ⇒ \quad A \times B \subseteq C \times D \tag{1}$$ How do you prove such an implication ? You assume the left-hand side to be true.
Read more
Positive: 12 %
ax²+bx+c; add exponents- keep base; ... b further from the x axis; c quadratic; ... 5 Multiple choice questions. a⁴/b⁴. a⁵/a³=? 0⁰=? (a/b)⁴ ...
Read more
Positive: 10 %

Show more results